Kazakhstan Diagnostic Review of Consumer Protection in Financial Services : Volume 1. Key Findings and Recommendations - World Bank (World Bank, Washington, DC, 2017)
From 2004 to 2007, lending to households in Kazakhstan expanded rapidly at 116 percent average annual growth rate and reached 22 percent of GDP, with loans in foreign currency reaching 7 percent of GDP. The share of real estate lending doubled between 2004 and 2007, amounting to 30 percent of GDP at end-2007.Following the global financial crisis and depreciation of the Kazakh tenge, the ratio of nonperforming loans to total loans in housing and mortgage increased from 5 percent in 2008 to 30 percent in 2010. This massive disruption highlighted the need for strong consumer protection and financial capability. Kazakh banks, which had relied extensively on capital market funding, attempted to shrink the credit portfolio and increase domestic deposits with limited success since most adult Kazakhs still have no access to formal financial services, due to low trust and low incomes. The government of Kazakhstan has developed a program to build confidence in the financial sector among investors and consumers. This World Bank’s diagnostic review, conducted in support of the program, is presented in two volumes. Volume I discusses the importance of financial consumer protection, summarizes the Kazakh government`s policy, and sets out the key findings and recommendations of the Review. Volume II provides an assessment of financial consumer protection in the four key segments of the Kazakhstan’s financial sector—banking, securities, insurance, and private pensions.